TEACHING ENGLISH USING STORYBOOK READING AT SDN 1 PURWODADI GROBOGAN IN THE 2004 CURRICULUM - APRILIYANINGRUM, DEWI (2007)
The objectives of this paper are to describe the process of teaching English using storybook reading, to describe the problems faced by the teacher, and to know the student's comment on the implementation of teaching English using storybook reading at the fifth year of SD Negeri 1 Purwodadi Grobogan. The writer focuses on the English vocabulary teaching learning process. The data are taken from observation in the classroom and interview with the English teacher and a lso the fifith year students of SD Negeri 1 Purwodadi Grobogan. Based on the research finding, the conclusion can be drawn as follows : (1) the teacher uses storybook reading to teach English lesson, there are four storybooks which are read by the teacher, namely: "The Silk Shawl Girl", "What a Painful Lesson", "The True Love of The Turtle Baby", and "The Foolish Birds"; (2) there are some problems faced by the teacher in teaching English using storybook reading, namely the teacher sometimes doesn't master the target language perfectly, it is difficult for the teacher to provide some different interesting activities in real situation into the classroom, it needs more energy and time to teach English, it is difficult for the teacher to manage the students i n the class, the teacher spend much money to get the material; and (4) the fifth year students of SD Negeri Purwodadi 1 Grobogan are enthusiastic in following the Engish lesson using storybook reading.